Harmonization of Religion and State : Mainstreaming the Values of Religious Moderation in Indonesian Da'wah Orientation - Husaini Husaini; Athoillah Islamy (Al-Adalah: Jurnal Hukum dan Politik Islam, 2022)
The problem of the motive or ideological pattern of da'wah that is scattered, both in the real and virtual world, has prompted the Indonesian Ulema Council (MUI) in 2017 to set guidelines for preachers in Indonesia. These guidelines are intended to be a code of ethics for da'i who carry out da'wah activities in Indonesia. This qualitative research in the form of a literature study intends to identify the dimensions of mainstreaming religious moderation values in the orientation of da'wah in Indonesia as formulated by the MUI. This study uses a normative-philosophical approach. The analytical theory used, namely four indicators of religious moderation formulated by the Ministry of Religion of the Republic of Indonesia in the form of anti-radicalism values, national commitment, tolerance, and accommodative to local culture. The results of the study conclude that there are dimensions of mainstreaming religious moderation values, dimensions of religious moderation values in da'wah orientation in Indonesia which were formulated by the Indonesian Ulema Council. First, the value of anti-radicalism in the orientation of religious-humanist Islamic religious character formation. Second, the value of national commitment and tolerance in the orientation of forming a nationalist and pluralist Islamic religious character. Third, the accommodative value of culture in the orientation of forming an innovative and harmonious Islamic religious character. The theoretical implication of this research shows that the prophetic Islamic social values contained in the da'wah orientation can be objectified in the life of a country that has a pluralistic social and religious background.